Altered Levels of Decidual Immune Cell Subsets in Fetal Growth Restriction, Stillbirth, and Placental Pathology - Bezemer, Romy E.; Schoots, Mirthe H.; Timmer, Albertus; Scherjon, Sicco A.; Erwich, Jan Jaap H. M.; van Goor, Harry; Gordijn, Sanne J.; Prins, Jelmer R. (Frontiers in Immunology, 2020)
Immune cells are critically involved in placental development and functioning. Inadequate regulation of the immune system is associated with placental pathology and pregnancy complications. This study aimed to explore numbers of decidual immune cells in pregnancies complicated with fetal growth restriction (FGR) and stillbirth (SB), and in placentas with histopathological lesions: maternal vascular malperfusion, fetal vascular malperfusion, delayed villous maturation, chorioamnionitis and villitis of unknown etiology. Placental tissue from FGR (n=250), SB (n=64) and healthy pregnancies (n=42) was included. Histopathological lesions were classified according to criteria developed by the Amsterdam Placental Workshop Group. Tissue slides were stained for CD68 (macrophages), CD206 (M2-like macrophages), CD3 (T cells), FOXP3 (regulatory T (Treg) cells), and CD56 (natural killer (NK) cells). Cell numbers were analyzed in the decidua basalis using computerized morphometry. The Mann-Whitney U test and Kruskal Wallis test with the Dunn’s as post-hoc test were used for statistical analysis. Numbers of CD68+ macrophages were higher in FGR compared to healthy pregnancies (p<0.0001), accompanied by lower CD206+/CD68+ ratios (p=0.002). In addition, in FGR higher numbers of FOXP3+ Treg cells were seen (p=0.004) with elevated FOXP3+/CD3+ ratios (p=0.008). Similarly, in SB elevated FOXP3+ Treg cells were found (p=0.032) with a higher FOXP3+/CD3+ ratio (p=0.007). Furthermore, a trend towards higher numbers of CD68+ macrophages was found (p=0.099) in SB. Numbers of CD3+ and FOXP3+ cells were higher in placentas with villitis of unknown etiology compared to placentas without lesions (p=0.003 and p<0.0001), accompanied by higher FOXP3+/CD3+ ratios (p=0.004). Elevated number of macrophages in FGR and SB suggest a role for a macrophage surplus in the pathophysiology of these adverse pregnancy outcomes. A lower M2/total macrophage ratio in FGR could indicate the involvement of inflammatory macrophages specifically. The elevated levels of FOXP3+ Treg cells with higher Treg/total T cell ratios in FGR and SB may be associated with the abundant presence of specific placental lesions within the cohorts. More research on the functionalities of these cells in pregnancy complications is needed.